Economic valuation of Pade'an Hamlet mangrove forest, Jarangan Village, Rejoso District, Pasuruan Regency, Indonesia - Jannah, Thoriqul; Rafsanzani, Ivan Aprilio; Rachmawati, Nabila; Cynthia, Afifah Fitri (Journal of Marine Resources and Coastal Management, 2022)
The mangrove ecosystem has enormous benefits for the community, especially for people who live on the coast, including the mangroves in the Pade'an Hamlet, Jarangan Village, Rejoso District, Pasuruan Regency. This study aims to determine the economic value of mangrove forest in Pade’an Hamlet area using total economic value approach. This study used descriptive analysis to explain the activity of utilizing the natural resources of the mangrove ecosystem and quantitative analysis to calculate the total economic value of the mangrove ecosystem. The economic value of mangrove forests in the Pade'an Hamlet area per year is IDR 10,092,881,400.00. The total economic value obtained from the direct-use value (utilization of the fisheries sector) amounted to IDR 7,593,550,000.00/year, indirect-use value (abrasion restraints) amounted to IDR 2,335,952,000.00/year, option value (biodiversity) amounted to IDR 13,379,400.00/year, and existence value calculated from the willingness to pay of the local community is IDR 150,000,000.00/year. The magnitude of the total economic value of the mangrove ecosystem in Pade’an Hamlet area indicates that the mangrove ecosystem provides huge of essential benefits to the community.